1995
DOI: 10.1007/s00585-995-0919-9
|View full text |Cite
|
Sign up to set email alerts
|

High spatial and temporal resolution observations of the ionospheric cusp

Abstract: Abstract. The Halley PACE HF radar has been operated in a new mode to provide very high time (10 s) and space (15 km) resolution measurements of the iono-spheric signatures of the cusp and the low-latitude boundary layer. The first data show that the iono-spheric signature of flux transfer events occur up to 300 km equatorward of regions showing the HF characteristics of the ionospheric cusp. Whilst larger flux transfer events are seen, on average, every 7 min, many much smaller and short-duration events have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 0 publications
10
110
2
Order By: Relevance
“…A key and unique prediction of this model is that patches of newly opened flux, produced by successive reconnection pulses, are appended to each other in a contiguous manner, causing discontinuous steps in the cusp ion dispersion on the boundaries between poleward moving events. The observation of these "cusp ion steps" in association with poleward moving events [Lockwood et al, 1993b;Pinnock et al, 1995] The two-dimensional reconnection pulse is similar in many ways to the flux rope model from which it evolved. Indeed, if the reconnection X line is short, this model can re-produce the "elbow" of newly opened field lines of the fossil flux tube model [Seinenov et al, 1995].…”
Section: Two-dimensional (2-d) Reconnection Pulse Modelmentioning
confidence: 82%
“…A key and unique prediction of this model is that patches of newly opened flux, produced by successive reconnection pulses, are appended to each other in a contiguous manner, causing discontinuous steps in the cusp ion dispersion on the boundaries between poleward moving events. The observation of these "cusp ion steps" in association with poleward moving events [Lockwood et al, 1993b;Pinnock et al, 1995] The two-dimensional reconnection pulse is similar in many ways to the flux rope model from which it evolved. Indeed, if the reconnection X line is short, this model can re-produce the "elbow" of newly opened field lines of the fossil flux tube model [Seinenov et al, 1995].…”
Section: Two-dimensional (2-d) Reconnection Pulse Modelmentioning
confidence: 82%
“…The identi®cation of high-speed¯ow bursts such as these has been the most commonly used method to identify pulsed cusp footprint signatures in the radar data in previous studies of the ionospheric footprint of the magnetospheric cusp (e.g. Pinnock et al, 1995;Rodger and Pinnock, 1997;Provan et al, 1998;Neudegg et al, 1999).…”
Section: Selecting the Pif Intervalsmentioning
confidence: 99%
“…The e ect of the IMF B y component on this average distribution is discussed in Provan et al (1998). They showed that the statistical location of PIFs is strongly dependent on IMF conditions, moving to the pre-noon sector during intervals of positive IMF B y and into the post-noon sector during intervals of negative IMF B y .…”
Section: Statistical Characteristics Of Pifsmentioning
confidence: 99%